BULLYING IN SCHOOL - PREVENTION AND INTERVENTION STRATEGIES - Luminița Mihaela DRĂGHICESCU; Ioana STĂNCESCU (National Centre for Policy and Evaluation in Education, 2019)
In a world that seems to lose its axiological landmarks, in which conflicts and aggressiveness are present at any level of society, in various forms, the school is no longer a safe and positive environment for either children or teachers. Bullying is a phenomenon that is implied into school life, having negative effects on the physical and mental health of children, on their personality, as well as on the quality of the educational process. In this context, through our study, we intend to investigate the extent to which teachers, being aware of the seriousness of the actions subsumed by bullying, are intervening promptly, adopting a series of strategies to prevent and/or combat this phenomenon. At the level of the European Union and beyond, there is an obvious concern for preventing and limiting the school bullying. Consequently, through our investigative approach, in which we included a group of teachers from pre-university education, we also aim to identify the extent to which they are aware of the need for involvement, in order to promote a safe educational climate, to ensure the physical and emotional security of their students. The results of our research revealed a proactive attitude on behalf of the teachers, who were aware of the importance of their intervention for the development of harmonious relationships among students, for the training/development of their socio-emotional competences, as well as for diminishing/stopping bullying, through mediation, appropriate sanctions, effective collaboration with all the educational partners.